DRUG-INDUCED CUTANEOUS LUPUS ERYTHEMATOSUS - Vasco Coelho Macias; Sónia Fernandes; Rubina Alves; Cândida Fernandes; Gabriela Marques Pinto; Jorge Cardoso (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Statins are widely used nowadays. They are usually safe but sometimes can be associated with the development/ worsening of autoimmune diseases like Cutaneous Lupus Erythematosus. Authors describe the case of a female caucasian patient, 74 years-old, that 18 months after initiating therapy with simvastatin developed an annular skin rash on back and shoulders, characterized by erythematous papules and plaques with a desquamative surface. Laboratory tests showed positive ANA and anti-SSA antibodies. Skin biopsy was consistent with clinical diagnosis of Subacute Cutaneous Lupus Erythematosus. The clinical picture had complete resolution after Simvastatin cessation. Drug-induced Cutaneous Lupus Erythematosus is often very similar to idiopathic forms. Although it usually has a favorable prognosis, authors highlight its importance because of the possible associated systemic manifestations and disfiguring cutaneous scars.